Keterampilan Komunikasi Verbal Guru Dalam Pembelajaran PAI Di SD N 02 Magek - Intan Wulan Sari; Salmiwati Salmiwati; Wedra Aprison; Darul Ilmi (Badan Penerbit STIEPARI Press, 2023)
This study discusses how the teacher's Verbal Communication skills in PAI learning at SD N 02 Magek and so that it can be known what are the obstacles experienced by PAI teachers at SD N 02 Magek. This study uses a qualitative descriptive method, which is a field research with data collection techniques through observation, interviews, and documentation. In this study, the key informant was the Islamic Religious Education Subject teacher. The next step the author took was data analysis by examining all existing data from various sources, then making data reduction by making abstractions. Judging from the results of interviews and observations of the author at SD N 02 Magek, the teacher's verbal communication at SD N 02 Magek is not optimal, the reason is because there are still teachers who speak using harsh language, it is because students are difficult to manage and don't want to carry out assignments then make the teacher's emotions become unstable, so that the teacher who speaks harshly can affect the personality of students who have a weak mentality..